Engineering design and performance validation of a low-cost diesel common rail injector test bench - Wedhar Adi Wiratama; Zainal Arifin; Sudarwanto; Ware-Ebi Guwor-Niki Jesse (Universitas Negeri Yogyakarta, 2026)
High-pressure common rail (HPCR) systems are essential in modern diesel engines to meet performance and emissions requirements. However, commercial injector test benches remain costly for vocational laboratories and small-scale workshops. This study designs, develops, and preliminarily validates a low-cost diesel common rail injector test bench using the ADDIE (analysis, design, development, implementation, and evaluation) framework. The system integrates a repurposed Chevrolet Captiva high-pressure supply pump driven by a 1 hp AC motor, a high-pressure fuel circuit, and an Arduino Nano-based electronic control unit (ECU) that applies pulse-width modulation (PWM) to control pulsed injector actuation. Validation was performed using a Denso Hino RN285 injector at low, medium, and high operating stages. The bench generated rail pressures from 360 bar (36 MPa) to 850 bar (85 MPa) and delivered 18.0 to 39.0 mL of fuel over a 20 s collection window. The measured delivery volume at low and medium speeds remained within the manufacturer’s tolerance after interpolation to the actual measured rpm. In contrast, a delivery deficit was observed at the highest speed. Quantitative spray-image analysis yielded spray angles of 15.38-20.44 degrees, within the specified range. The results indicate that the developed bench is a functional laboratory-scale platform for injector diagnostics and vocational training, although further benchmarking against calibrated commercial equipment and long-term durability testing are still required.